EFECTOS DEL DIETILESTILBOESTROL SOBRE LA RESPUESTA VASCULAR RENAL DE LA RATONA A LA VASOPRESINA - SOTO VERGARA, EDUARDO; GUTIERREZ NAVA, ROGELIO (Instituto Nacional de Cardiología, CD MEXICO, DF, MEX, 1943)
Stained blood cells were studied in cases of neutrophilic gran-ulocytosis When the toxic lesions were slight there were only abnormalities in the neutrophilic granules, the granulations of Monsen, and the small and somewhat numerous basophilic inclusions
BOL INST ESTUD MED BIOL
Keywords: EFECTOS, DIETILESTILBOESTROL, RESPUESTA, VASCULAR, RENAL, VASOPRESINA; CIENCIAS MEDICAS; FARMACOLOGIA; FARMACOLOGIA EXPERIMENTAL